2015
DOI: 10.1186/s12906-015-0785-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the antidiabetic effects of Chinese herbal medicine: Xiao-Ke-An in 3T3-L1 cells and KKAy mice using both conventional and holistic omics approaches

Abstract: BackgroundXiao-Ke-An (XKA) is a Chinese medicine widely used for treating type 2 diabetes mellitus (T2D). It is composed of eight herbal medicines traditionally used for T2D, including Rehmannia glutinosa Libosch, Anemarrhena asphodeloides Bunge, Coptis chinensis Franch, etc. The aim of the present study was to investigate the antidiabetic effects of XKA with both conventional and holistic omics approaches.MethodsThe antidiabetic effect of XKA was first investigated in 3T3-L1 cells to study the effect of XKA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…By manually text-mining the published literatures in Pubmed, the anti-CCVD effects of these constituents in XST were summarized. The anti-CCVD effect was evaluated by Reverse Rate (RR) 48 , 49 , which was calculated by equation ( 1 ). where N j , M j and T j indicate the performances of normal, model and constituent treated group in report j .…”
Section: Methodsmentioning
confidence: 99%
“…By manually text-mining the published literatures in Pubmed, the anti-CCVD effects of these constituents in XST were summarized. The anti-CCVD effect was evaluated by Reverse Rate (RR) 48 , 49 , which was calculated by equation ( 1 ). where N j , M j and T j indicate the performances of normal, model and constituent treated group in report j .…”
Section: Methodsmentioning
confidence: 99%
“…The neologism “-omics,” including genomics, proteomics, and metabolomics, refers to the collective characterization and quantification of pools of biological molecules that translate into the structure, function, and dynamics of an organism ( Kedaigle and Fraenkel, 2018 ). The current “-omics” studies provide new opportunities for the potential future development of the CHM ( Yang et al, 2015 ). In the last decade, significant developments have been achieved in epigenomics studies, focusing on the complete set of epigenetic modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Ber offers potential for the treatment of type 2 diabetes mellitus (T2DM) (2-7), whereas CCE is primarily one of the components of a Chinese traditional formula for the treatment of diabetes mellitus (DM) via the prevention of associated vascular and cardiac damage, renal fibrosis and lipid metabolism (8)(9)(10). Ber is a classical natural medicine, the applications of which have attracted interest in investigations focused on the treatment of DM (11)(12)(13)(14)(15). The pharmacological effects of Ber on glucose metabolism…”
Section: Introductionmentioning
confidence: 99%